Distribution Dynamics and Roles of Starch in Non-photosynthetic Vegetative Organs of Santalum album Linn., a Hemiparasitic Tree - Zhou, Xiu Ren; Zhang, Ning Nan; Zhao, Yi Min; Dai, Lei; Xu, Da Ping; Xu, Gui Fang; Tian, Jing (Frontiers in Plant Science, 2021)
Allocation dynamics of stored starch plays essential roles in the development and growth of trees. Previous studies focused on the dynamics and the characteristics of starch in autotrophic trees. However, although starch granules have been detected in the organs or tissues of some parasitic plants, studies on the allocation dynamics and roles of storage starch in them are limited. Therefore, we determined and estimated the allocation dynamics and roles of starch in Santalum album Linn., a hemiparasitic tree, using morphological and physiological methods. Our findings showed abundant starch in the stem and root of S. album at the early seedling stage. Although S. album seedlings attached to the host showed no significant changes in starch levels throughout the experiment, unattached and host-removed seedlings exhibited a gradual decrease in the starch content over time. When the starch content of unattached seedlings was less than 1%, they started to die. Starch accumulated to high levels in developing and active haustoria; however, starch levels were low in the inactive haustoria. The present study suggests that starch may provide energy to seedlings that have no host, allowing them to survive during the unattached phase, thus increasing their chance to attach to host roots by extending their survival duration. In addition, we speculate that storage starch is potentially involved in the development of haustoria and in the physiological processes of S. album related to the absorption and transportation of water and nutrients from its host.